Sexuality Discourse in Contemporary Yoruba Music: A Study of Abass Akande ‘Obesere’ and Janet Ajilore ‘Saint Janet’ - Ademowo, Adeyemi J.; Balogun, Noah O. (Àgídìgbo: ABUAD Journal of the Humanities, 2017)
Sexuality is a central aspect of human life that encompassessex, gender, identities and roles, sexual orientation, eroticism, pleasure, intimacy and reproduction. It is experienced and expressed in thoughts, fantasies, desires, beliefs and, in some cases, misinterpreted as nothing but vulgarity. The desire to preserve the ‘sanctity’ of the Yoruba language so that it will remain ‘morally clean’ despite its use in music has made sexuality discourse in music a discouraged subject among the Yorubas. Hence, the derision of sexuality related discourses on the public space. Using Foucault’s theory ofsexuality embodied in his history of sexuality as a foil, we aver that the stigmatization of Obesere and Saint Janet’s music as “immoral” and ‘not fit for the ears’ is basically because they both frustrate efforts to control sex at the level of speech, and inadvertently intensify discourses on sex, sexual performance and the power relations among Yoruba men and women which all had concomitant effects on morals on and off the public space.